Kapitał społeczny – krótkie losy pojęcia - Banaszak, Sławomir (Studia Edukacyjne, 2018)
The paper deals with the concept of social capital. The author tries to show the phenomena and processes that the concept expresses. The paper adopts a critical attitude towards the social capital concept. The author argues that social capital, through its complexity and extremely synthetic character, requires to be divided into narrower and more specific concepts that directly refer to the important phenomena and processes of the modern world: education, culture, and economy.